Integration of the rights to health and food as human rights in the national policy of indonesia’s free nutritious meal program - Noor Azizah; Hanafi Hanafi; Sri Herlina (International Journal of Law, Environment, and Natural Resources, 2026)
Health development in Indonesia continues to face major challenges, particularly in fulfilling community nutrition needs, as reflected in the high prevalence of stunting, wasting, and malnutrition. From a human rights perspective, the rights to health and food are interrelated and require integrated policy implementation. Through the Free Nutritious Meal Program (MBG), the government seeks to fulfill nutritional needs while carrying out its responsibility to guarantee the rights to health and food. This study aims to analyze the regulation of the rights to health and food within the Indonesian legal system and examine the integration of both rights into the Free Nutritious Meal Program as a human rights–based policy using normative legal research methods with statutory, conceptual, and human rights approaches. The findings show that the rights to health and food already have a strong normative basis in the 1945 Constitution and related legislation; however, existing regulations remain sectoral and lack an integrated framework. The study also identifies potential conflicts between fulfilling the rights to health and food and the right to education, particularly regarding state budget allocation, as the Free Nutritious Meal Program may create budgetary pressure on the education sector, thereby requiring regulatory harmonization to ensure balanced fulfillment of all human rights.